Young people in uncertain labor markets international evidence - Yeung, Wei-jun Jean 1958-; Yang, Yi; Kalleberg, Arne L. (SAGE, 2020)
Labor market uncertainties for youth and young adults : an international perspective / Wei-Jun Jean Yeung, Yi Yang -- Unemployment patterns of local-born and migrant youth in a postcolonial society : a double cohort analysis / Kumiko Shibuya, Hua Guo, Eric Fong -- Youth labor market prospects in times of economic recession in Brazil / Arnaldo Mont'Alvao, Carlos Costa Ribeiro -- Who can access the "good" jobs? Racial disparities in employment among young men who work in paid care / Shengwei Sun -- Navigating an uncertain labor market in the UK : the role of structure and agency in the transition from school to work / Ingrid Schoon -- China's college expansion and the timing of the college-to-work transition : a natural experiment / Lingxin Hao, Dong Zhang -- Changes in early labor market outcomes among young college graduates in South Korea / Jaesung Choi, Hannah Bae -- Young women's transition from education to work in the Caucasus and Central Asia / Michael Gebel -- From education to the labor market in Lithuania : the role of youth and parental education / Ruta Braziene -- China's youth in neet (not in education, employment, or training) : evidence from a national survey / Yi Yang -- Youth education and employment in Mexico City : a mixed-methods analysis / Gabriela Sánchez-Soto, Andrea Bautista León -- Heterogeneity among young people neither in employment nor in education in Brazil / Tamille Sales Dias, Ana Maria Nogales Vasconcelos -- Job instability and fertility intentions of young adults in Europe : does labor market legislation matter? / Tatiana Karabchuk -- Does early career unemployment at the peak of a recession leave economic scars? Evidence from Estonia / Marge Unt, Kadri Täht -- Labor market uncertainties and youth labor force experiences : lessons learned / Arne L. Kalleberg
Includes bibliographical references
Keywords: Prekariat; Junger Arbeitnehmer; Youth / Employment; Labor market; Youth; Employment